Conductive film, method for manufacturing conductive film, and method for manufacturing connection structure

A two-layer conductive film with specific resin viscosity ratios and particle positioning stabilizes particle capture and conduction resistance on substrates with undulations and small pads, addressing the limitations of existing anisotropic conductive films.

JP2025013237APending Publication Date: 2025-01-24DEXERIALS CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024108536
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-14
Filing Date
2024-07-05
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing anisotropic conductive films face challenges in stabilizing the number of captured particles with large diameter particles, especially when applied to substrates with undulations and small connection pads, leading to issues with conductive resistance and short circuits.

Method used

A two-layer conductive film structure is introduced, comprising an insulating high-viscosity resin layer and a low-viscosity resin layer with conductive particles, where the conductive particles are arranged closer to the high-viscosity resin layer, maintaining a viscosity ratio of 7:4 or more, and positioned to minimize resin flow during pressing.

Benefits of technology

The two-layer structure enhances the number of captured particles, ensuring stable conduction resistance and effective connections on substrates with undulations and small connection pads, reducing the risk of short circuits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025013237000001_ABST
    Figure 2025013237000001_ABST
Patent Text Reader

Abstract

To obtain a conductive film capable of increasing the number of captured particles and being applicable to a ceramic substrate having an undulation and a substrate having a small connection pad.SOLUTION: A conductive film includes an insulating high-viscosity resin layer, an insulating low-viscosity resin layer, and conductive particles having an average particle diameter of 13 μm or more, the low-viscosity resin layer is laminated on the high-viscosity resin layer, the viscosity ratio between the high-viscosity resin layer and the low-viscosity resin layer at 80°C is 7:4 or more, and the conductive particles are disposed on the high-viscosity resin layer side from a position where 2 / 3 of the particle diameter protrudes toward the low-viscosity resin layer side from the boundary between the high-viscosity resin layer and the low-viscosity resin layer.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a conductive film, a method for manufacturing a conductive film, and a method for manufacturing a connection structure, and more particularly to a large-diameter particle aligned anisotropic conductive film, which is a large-diameter particle aligned conductive film. [Background technology]

[0002] Anisotropic conductive films are widely used when mounting electronic components on a substrate. In recent years, the density of components in smartphones and other devices has increased, resulting in space restrictions within the case. In particular, in camera modules, cameras have become larger and more multi-lens, and the size of imager substrates has increased to improve image accuracy. On the other hand, connection pads have become smaller, and it is required to obtain more stable conductive resistance values ​​even with the small connection area in this application. Ceramic substrates are used for camera modules, and large-diameter particles are sometimes used in anisotropic conductive films to take into account the unevenness and steps of the substrate. In addition, in the case of large-diameter particles, dispersed anisotropic conductive films (hereinafter, dispersed ACF) have problems with the corresponding area and short circuits, so anisotropic conductive films with regularly arranged conductive particles in a planar view of the film (aligned ACF) are required.

[0003] For example, Patent Document 1 describes an anisotropic conductive film that is a filler-containing film having a filler dispersion layer in which a filler is dispersed in a resin layer, and the surface of the resin layer near the filler has a recess with respect to the tangent plane of the resin layer at the center between adjacent fillers. Patent Document 2 also describes an anisotropic conductive film that includes an insulating adhesive layer and conductive particles regularly arranged in the insulating adhesive layer in a planar view, in which the conductive particle diameter is 13 μm or more, the thickness of the film is equal to or greater than 3.5 times the conductive particle diameter, the variation width of the conductive particle position in the thickness direction of the film is less than 10% of the conductive particle diameter, 10 areas with an area of ​​1 mm×1 mm are extracted in the longitudinal direction of the anisotropic conductive film, and the difference between the maximum and minimum values ​​when the particle density in the planar view of each area is measured is less than 20% of the average particle density of each area, and further, another insulating adhesive layer different from the insulating adhesive layer in which the conductive particles are regularly arranged in a planar view is laminated. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-031649 A [Patent Document 2] JP 2019-087536 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, the anisotropic conductive films of Patent Documents 1 and 2 have room for further improvement in terms of stabilizing the number of captured particles with the minimum connection area when large-diameter particles are used. There is also room for improvement in conductive films from the viewpoint of capturing particles at intended locations.

[0006] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a conductive film or an anisotropic conductive film that can increase the number of captured particles and that can be used with wavy ceramic substrates and substrates with small connection pads. [Means for solving the problem]

[0007] The inventors of the present invention found the following and came up with the present invention. That is, in order to maintain a more stable conductive resistance value in a conductive film (anisotropic conductive film), it is good for the quality stability of the connection structure that a certain number of particles or more are captured for each terminal (connection pad) and the number of particles captured for each connection pad for each connection structure is stable within a certain range, but in the case of a single layer using large diameter particles, there is a limit to the improvement of particle capture by controlling the viscosity alone. When it is desired to improve particle capture in a single layer, it is also effective to change the particle arrangement of regularly arranged conductive particles, but in order to ensure higher particle capture, it is preferable to use a two-layer product with a viscosity difference. On the other hand, in a camera module substrate using a wavy ceramic substrate, it is difficult to use small diameter particles less than 13 μm to eliminate the height difference caused by the wavy substrate, so it is more desirable to use large diameter particles of 13 μm or more and then make a two-layer product.

[0008] The conductive film of the present invention comprises an insulating high-viscosity resin layer, an insulating low-viscosity resin layer, and conductive particles having an average particle diameter of 13 μm or more, the low-viscosity resin layer being laminated on the high-viscosity resin layer, the viscosity ratio between the high-viscosity resin layer and the low-viscosity resin layer at 80°C being 7:4 or more, and the conductive particles being arranged on the high-viscosity resin layer side from a position where 2 / 3 of the particle diameter protrudes toward the low-viscosity resin layer side from the boundary between the high-viscosity resin layer and the low-viscosity resin layer.

[0009] A method for producing a conductive film of the present invention includes attaching regularly arranged conductive particles with an average particle diameter of 13 μm or more to a surface of an insulating high-viscosity resin layer, burying the conductive particles in the high-viscosity resin layer while applying heat and pressure to the surface of the high-viscosity resin layer to which the conductive particles are attached, and disposing and pressing an insulating low-viscosity resin layer on the surface side of the high-viscosity resin layer to which the conductive particles are embedded, or attaching regularly arranged conductive particles with an average particle diameter of 13 μm or more to the surface of an insulating low-viscosity resin layer, and applying heat and pressure to the surface of the low-viscosity resin layer to which the conductive particles are attached. The conductive particles are embedded in the low-viscosity resin layer while applying pressure, and an insulating high-viscosity resin layer is disposed on the surface side of the low-viscosity resin layer where the conductive particles are embedded, and the resin is pressed against the conductive particles. The resin includes the high-viscosity resin layer, the low-viscosity resin layer, and the conductive particles, and the low-viscosity resin layer is laminated on the high-viscosity resin layer, and the viscosity ratio of the high-viscosity resin layer to the low-viscosity resin layer at 80°C is 7:4 or more, and the conductive particles are disposed on the high-viscosity resin layer side from a position where 2 / 3 of the particle diameter protrudes from the boundary between the high-viscosity resin layer and the low-viscosity resin layer toward the low-viscosity resin layer side. Note that the pressing during the manufacturing method of the conductive film is different from the pressing during the connection process. The temperature and pressure do not affect the product life of the conductive film.

[0010] In addition, the manufacturing method of the connection structure of the present invention includes a joining step of electrically joining a first electronic component and a second electronic component with a conductive film, the conductive film includes an insulating high-viscosity resin layer, an insulating low-viscosity resin layer, and conductive particles having an average particle diameter of 13 μm or more, the low-viscosity resin layer is laminated on the high-viscosity resin layer, the viscosity ratio of the high-viscosity resin layer to the low-viscosity resin layer at 80°C is 7:4 or more, and the conductive particles are arranged on the high-viscosity resin layer side from a position where 2 / 3 of the particle diameter protrudes toward the low-viscosity resin layer side from the boundary between the high-viscosity resin layer and the low-viscosity resin layer. Effect of the Invention

[0011] The conductive film of the present invention is a particle-arranged ACF using large-diameter particles, and is a two-layer film with a viscosity difference, which makes it possible for the conductive film of the present invention to increase the number of captured particles and to be used on wavy ceramic substrates and substrates with small connection pads. [Brief description of the drawings]

[0012] [Figure 1] 1 is a plan view of an anisotropic conductive film (conductive film) according to an embodiment. [Diagram 2] 1 is a cross-sectional view of an anisotropic conductive film (conductive film) according to an embodiment. [Diagram 3] FIG. 13 is a diagram showing a schematic diagram of temporary attachment during pressure bonding. [Figure 4] 1 is a cross-sectional view of an anisotropic conductive film (conductive film) of Example 3. FIG. [Diagram 5] 1 is a cross-sectional view of an anisotropic conductive film (conductive film) of Comparative Example 2. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] A detailed description will be given of a form (embodiment) for carrying out the present invention. The present invention is not limited to the contents described in the following embodiment. Furthermore, the components described below include those that a person skilled in the art can easily imagine and those that are substantially the same. Furthermore, the configurations described below can be appropriately combined. Furthermore, various omissions, substitutions, or modifications of the configuration can be made without departing from the gist of the present invention. The following description of the present invention will be centered on an anisotropic conductive film, but it may also be considered that the present invention is also applicable to conductive films.

[0014] Specifically, the configuration, characteristics, and manufacturing method of the anisotropic conductive film of the embodiment will be described below. It may be considered that these configurations, characteristics, and manufacturing methods are also applicable to the conductive film. The conductive film includes anisotropic conductive films and isotropic conductive films, but even if it is the same conductive film, it may be considered as an anisotropic conductive film exhibiting anisotropic conductivity depending on the connection object, and may also be considered as a conductive film (conductive particle-containing adhesive film, bonding film). In addition, from the viewpoint of the recent demand for the complication of the configuration (various dimensions) and layout of the electrodes (terminals, connection pads, pads) of electronic components, it may be difficult to distinguish them. Furthermore, the manufacturing method of the connection structure of the embodiment will be described below in the case where the above anisotropic conductive film is used. It may be considered that this manufacturing method is also applicable to the case where the above conductive film is used.

[0015] Fig. 1 is a plan view of an anisotropic conductive film according to an embodiment, and Fig. 2 is a cross-sectional view of the anisotropic conductive film according to an embodiment. The anisotropic conductive film 1 includes an insulating high-viscosity resin layer 11 and an insulating low-viscosity resin layer 12 as an insulating resin layer 10, and conductive particles 20, and the low-viscosity resin layer 12 is laminated on the high-viscosity resin layer 11. Fig. 2 is a cross-sectional view taken along line AA in Fig. 1. The cross-sectional view taken along line AA passes through the center of the conductive particles 20. The anisotropic conductive film according to an embodiment can be in the form of a long film, for example, 5 m or more in length, and can also be wound around a core to form a wound body.

[0016] As shown in FIG. 1, in the anisotropic conductive film 1, the conductive particles 20 are regularly arranged in the resin layer 10 in a planar view. That is, they are arranged in a square lattice (tetragonal lattice) in a planar view. In this way, the regular arrangement of the conductive particles 20 in the anisotropic conductive film 1 is preferably arranged regularly so that there is no variation in density in the planar arrangement of the conductive particles 20. For example, it is preferable that 10 areas each having an area of ​​1 mm×1 mm are extracted in the longitudinal direction X of the film, and the difference between the maximum and minimum particle densities of the conductive particles in each area is less than 20% of the average particle density of each area. For this purpose, the conductive particles 20 may be arranged in a square lattice (tetragonal lattice), an oblique lattice, a rectangular lattice (rectangular lattice), a hexagonal lattice, or the like. When the conductive particles are regularly arranged, the conductive particles are easily captured by the terminals even if the connection surface on which the terminals are formed is wavy, and the occurrence of poor conduction and short circuits can be significantly reduced.

[0017] Furthermore, if the conductive particles are randomly dispersed, when a low particle density portion of the conductive particles is placed on a terminal on a convex portion of the undulations of the module substrate during an anisotropic conductive connection, the conductive particles on that terminal will flow, making the particle density of that portion even lower, reducing the number of conductive particles captured at the terminal and possibly causing poor conductivity (inadequate conductive performance).

[0018] In the anisotropic conductive film 1, the conductive particles 20 are arranged in a lattice, and the lattice axis B of the arrangement intersects with the longitudinal direction X from the viewpoint of stabilizing particle capture. For example, in the case of an anisotropic conductive film for fine pitch, the angle θ between the longitudinal direction X of the anisotropic conductive film 1 and the lattice axis B is preferably set to 10° to 40°. The lattice axis B may be parallel to the longitudinal direction X or the lateral direction Y of the anisotropic conductive film 1, and can be determined according to the terminal width, terminal pitch, etc.

[0019] The particle density of the conductive particles 20 is set to 20 particles / mm from the viewpoint of electrical conductivity reliability. 2 More preferably, 40 pieces / mm 2 More preferably, it is 150 pieces / mm 2From the viewpoint of electrical conductivity reliability, the particle density of the conductive particles 20 is preferably 2000 particles / mm 2 It is preferable that the number of pieces is 1500 pieces / mm or less. 2 More preferably, it is 850 pieces / mm or less. 2 It is even more preferable that the particle density (number density) of the conductive particles 20 is equal to or less than the above.

[0020] Regarding the regular arrangement of the conductive particles 20, if the center-to-center distance of adjacent conductive particles is too short, a short circuit is likely to occur, and if it is too long, the number of conductive particles captured by the terminal is insufficient, making it impossible to achieve a sufficient conductive connection. For this reason, it is necessary to achieve both short circuit prevention and stable conductive connection. From the viewpoint of ensuring a certain number of captured particles and improving the conductive stability, it is preferable that the center-to-center distance between the most closely adjacent conductive particles 20 is 1.2 times or more, more preferably 1.5 times, the average particle diameter. In addition, from the viewpoint of preventing a short circuit in which conductive particles are connected to each other and conduct electricity between terminals, it is preferable that the center-to-center distance between the most closely adjacent conductive particles 20 is 100 times or less, more preferably 80 times or less, the average particle diameter. It may be appropriately selected based on the conditions of the objects to be connected, such as the configuration and layout of the electrodes.

[0021] The average particle diameter of the conductive particles 20 is 13 μm or more in order to ensure stable conduction even when the surface is undulated, such as in a ceramic module substrate. From the viewpoint of the risk of short circuits, it is preferably 30 μm or less. The average particle diameter is determined by measuring 10,000 or more particles using a particle size distribution meter. It is preferable to measure with an image-type particle size distribution meter. In addition, when the conductive particles are spherical, the average diameter may be determined by measuring 200 or more particles in a planar view of the film.

[0022] The configuration of the conductive particles 20 themselves can be appropriately selected from those used in known anisotropic conductive films. For example, metal particles such as nickel, cobalt, silver, copper, gold, and palladium, and metal-coated resin particles in which core resin particles are metal-coated, can be used. Two or more types of conductive particles 20 can be used in combination. Here, the metal coating of the metal-coated resin particles can be formed by using a known metal film forming method such as an electroless plating method or a sputtering method. The core resin particles may be formed only from resin. The particles are preferably spherical, but may be protruding particles in which protrusions are formed on the surface of the particles. The surface of the conductive particles may be subjected to an insulating treatment by a known technique.

[0023] In the anisotropic conductive film 1, the viscosity ratio of the high-viscosity resin layer 11 to the low-viscosity resin layer 12 at 80°C (viscosity of the high-viscosity resin layer 11 at 80°C: viscosity of the low-viscosity resin layer 12 at 80°C) is 7:4 or more, and preferably 4:1 or more. This makes it possible to prevent the resin from flowing and reducing the ability to capture conductive particles when pressed during anisotropic conductive connection. In addition, the viscosity ratio of the high-viscosity resin layer 11 to the low-viscosity resin layer 12 is preferably 30:1 or less, and more preferably 10:1 or less. The above viscosity ratio can be restated as follows: In the anisotropic conductive film 1, the viscosity of the high-viscosity resin layer 11 at 80° C. / the viscosity of the low-viscosity resin layer 12 at 80° C. is 7 / 4 or more, and preferably 4 / 1 or more. Moreover, the viscosity of the high-viscosity resin layer 11 at 80° C. / the viscosity of the low-viscosity resin layer 12 at 80° C. is preferably 30 / 1 or less, and more preferably 10 / 1 or less.

[0024] The viscosity of the high-viscosity resin layer 11 is preferably 30000 Pa·s or less. Since an image sensor and a lens are mounted on the module substrate, the anisotropic conductive connection is usually performed under low-temperature and low-pressure conditions of a temperature of 190°C or less and a pressure of 2 MPa or less. When the viscosity of the high-viscosity resin layer 11 is within the above range, the anisotropic conductive connection can be suitably performed even under low-temperature and low-pressure conditions. In the anisotropic conductive film 1 in which the high-viscosity resin layer 11 and the low-viscosity resin layer 12 are laminated, the viscosity at 80°C is preferably 30000 Pa·s or less. Furthermore, in the anisotropic conductive film 1 in which the high-viscosity resin layer 11 and the low-viscosity resin layer 12 are laminated, the lower limit of the viscosity at 80°C is preferably 1000 Pa·s or more, and more preferably 2000 Pa·s or more.

[0025] The viscosity of the high-viscosity resin layer 11 is measured by melt viscosity measurement using a rotational rheometer (manufactured by TA Instruments) under conditions of a temperature rise rate of 10° C. / min, a constant measurement pressure of 5 g, and a measurement plate diameter of 8 mm, and is the viscosity value read at 80° C. The viscosity of the low-viscosity resin layer 12 can also be measured and read in the same manner. From these values, the viscosity ratio between the high-viscosity resin layer 11 and the low-viscosity resin layer 12 can be found.

[0026] From the viewpoint of the temporary attachment of the anisotropic conductive film to a substrate, the thickness of the high-viscosity resin layer 11 and the thickness of the low-viscosity resin layer 12 are each preferably ⅔ or more of the average particle diameter of the conductive particles 20. In addition, the total thickness of the high-viscosity resin layer 11 and the low-viscosity resin layer 12 is usually 3.5 times or less of the average particle diameter of the conductive particles 20.

[0027] As the high-viscosity resin layer 11 and the low-viscosity resin layer 12, insulating resin layers used in known anisotropic conductive films can be appropriately adopted. That is, they can be appropriately adopted so that the viscosity ratio between the high-viscosity resin layer 11 and the low-viscosity resin layer 12 is within the above range. For example, a photoradical polymerization type resin layer containing an acrylate compound and a photoradical polymerization initiator, a thermal radical polymerization type resin layer containing an acrylate compound and a thermal radical polymerization initiator, a thermal cationic polymerization type resin layer containing an epoxy compound and a thermal cationic polymerization initiator, a thermal anionic polymerization type resin layer containing an epoxy compound and a thermal anionic polymerization initiator, etc. can be used. In addition, these resin layers may be polymerized resin layers as necessary. In addition, in the case of a thermal radical polymerization type resin layer, it is preferable to use the thermal radical polymerization initiator in an amount of preferably 2 to 60 parts by mass, more preferably 5 to 40 parts by mass, relative to 100 parts by mass of the acrylate compound.

[0028] The high-viscosity resin layer 11 and the low-viscosity resin layer 12 preferably further contain a film-forming resin and a silane coupling agent. Examples of the film-forming resin include phenoxy resin, epoxy resin, unsaturated polyester resin, saturated polyester resin, urethane resin, butadiene resin, polyimide resin, polyamide resin, and polyolefin resin. Two types of film-forming resins can be used in combination. Among these, phenoxy resin is preferably used from the viewpoints of film-forming property, processability, and connection reliability. Examples of the silane coupling agent include epoxy-based silane coupling agents and acrylic-based silane coupling agents. These silane coupling agents are mainly alkoxysilane derivatives. The high-viscosity resin layer 11 and the low-viscosity resin layer 12 may further contain insulating fillers such as silica fine particles, alumina, and aluminum hydroxide, if necessary. For example, in the case of a thermal radical polymerization type resin layer, it is preferable to use 5 to 50 parts by mass of insulating filler relative to 100 parts by mass of acrylate compound. Furthermore, the high-viscosity resin layer 11 and the low-viscosity resin layer 12 may contain, in addition to the insulating filler described above, a filler, a softener, an accelerator, an antioxidant, a colorant (pigment, dye), an organic solvent, an ion catcher agent, etc.

[0029] The conductive particles 20 are arranged on the high-viscosity resin layer 11 side from the position where 2 / 3 of the particle diameter is protruding from the boundary C between the high-viscosity resin layer 11 and the low-viscosity resin layer 12 to the low-viscosity resin layer side. In this way, in the anisotropic conductive film 1, the conductive particles 20 are arranged at specific positions in the thickness direction Z, so that it is possible to prevent the resin from flowing and the trapping ability of the conductive particles from decreasing when the conductive particles are pushed in during anisotropic conductive connection. From the viewpoint of the trapping ability of the conductive particles, the conductive particles 20 are preferably arranged at a position where 1 / 2 of the particle diameter is protruding from the boundary C between the high-viscosity resin layer 11 and the low-viscosity resin layer 12 to the low-viscosity resin layer 12 side, or are arranged on the high-viscosity resin layer 11 side from the position where 1 / 2 of the particle diameter is protruding from the low-viscosity resin layer 12 side. Note that the conductive particles 20 may not protrude from the boundary C between the high-viscosity resin layer 11 and the low-viscosity resin layer 12, and may be arranged entirely on the high-viscosity resin layer 11 side. In other words, with respect to the boundary C between the high-viscosity resin layer 11 and the low-viscosity resin layer 12, the conductive particles 20 are embedded in the high-viscosity resin layer by more than ⅓ of their particle diameter. Furthermore, with respect to the boundary C, it is preferable that the conductive particles 20 are embedded in the high-viscosity resin layer by ½ or more of their particle diameter. Furthermore, with respect to the boundary C, it is more preferable that the conductive particles 20 are embedded in the high-viscosity resin layer by ⅔ or more of their particle diameter. Furthermore, with respect to the boundary C, the conductive particles 20 may be entirely embedded in the high-viscosity resin layer.

[0030] The fact that the conductive particles 20 are arranged at specific positions in the thickness direction Z can be confirmed, for example, as follows: The anisotropic conductive film 1 is cut at a cross section passing through the line AA in Fig. 1, and the cross section is observed by an electron microscope to confirm the positions of the conductive particles 20.

[0031] In the anisotropic conductive film 1, the variation in the positions of the conductive particles 20 in the thickness direction Z is preferably less than 10% of the average particle diameter. This variation is measured as the variation in the distance L between either one surface of the anisotropic conductive film 1 and each conductive particle 20. More specifically, first, 100 conductive particles 20 are consecutively extracted in the longitudinal direction X of the anisotropic conductive film 1, and the difference ΔL between the maximum and minimum values ​​of the distance L measured for each conductive particle 20 is obtained. Next, the variation can be calculated as the ratio of ΔL to the average particle diameter.

[0032] As described above, the anisotropic conductive film 1 has specific ranges for the average particle size of the conductive particles 20, the viscosity ratio between the high-viscosity resin layer 11 and the low-viscosity resin layer 12, and the position of the conductive particles 20 in the thickness direction Z. This makes it possible for the anisotropic conductive film 1 to prevent a decrease in the ability to capture conductive particles due to the resin flowing when pressed during anisotropic conductive connection. Therefore, the anisotropic conductive film 1 can increase the number of captured particles and is compatible with wavy ceramic substrates and substrates with small connection pads.

[0033] The anisotropic conductive film 1 can be manufactured by adhering the regularly arranged conductive particles having an average particle diameter of 13 μm or more to the surface of the insulating high-viscosity resin layer, embedding the conductive particles in the high-viscosity resin layer while applying heat and pressure to the surface of the high-viscosity resin layer to which the conductive particles are attached, and disposing and pressing the low-viscosity resin layer on the surface side of the high-viscosity resin layer to which the conductive particles are embedded. More specifically, the anisotropic conductive film 1 can be manufactured, for example, as follows. First, a mold having convex portions corresponding to the arrangement of the conductive particles 20 is manufactured on a flat metal plate by a method such as machining, laser processing, or photolithography. Next, the mold is filled with a curable resin and cured to manufacture a resin mold with an inverted concave and convex shape. This resin mold is used as a microcavity for conductive particles, and the conductive particles 20 are placed in the concave portions, and the high-viscosity resin layer 11 formed in advance is disposed on top of the conductive particles, and the high-viscosity resin layer 11 is peeled off with the conductive particles 20 attached to the surface. The conductive particles 20 are embedded in the high-viscosity resin layer 11 until they reach a desired position while applying heat and pressure to the surface of the high-viscosity resin layer 11 to which the conductive particles 20 are attached. A low-viscosity resin layer 12 formed in advance is disposed on the surface side of the high-viscosity resin layer 11 to which the conductive particles 20 are embedded, and is then pressed against the surface. In this manner, an anisotropic conductive film 1 as shown in FIG. 1 and FIG. 2 is obtained. When embedding the conductive particles 20 in the high-viscosity resin layer 11, the positions of the conductive particles 20 in the thickness direction Z can be set to a specific range by appropriately adjusting the heat and pressure applied. The conductive particles 20 may be attached to the surface of the low-viscosity resin layer 12 formed in advance to embed the conductive particles 20, and the high-viscosity resin layer 11 may be pressed against the surface side to which the conductive particles 20 are embedded. That is, the anisotropic conductive film 1 may be produced by adhering regularly arranged conductive particles having an average particle diameter of 13 μm or more to the surface of the insulating low-viscosity resin layer, embedding the conductive particles in the low-viscosity resin layer while applying heat and pressure to the surface of the low-viscosity resin layer to which the conductive particles are attached, and then disposing and pressing the high-viscosity resin layer on the surface side of the low-viscosity resin layer where the conductive particles are embedded.

[0034] <Method of Manufacturing Connection Structure> The manufacturing method of the connection structure of the embodiment includes a joining step of electrically joining a first electronic component and a second electronic component with the anisotropic conductive film described above. In detail, this step performs an anisotropic conductive connection between the connection terminal of the first electronic component and the connection terminal of the second electronic component. The width (short side) of the terminal (connection pad) suitable for anisotropic conductive connection is preferably 12 μm or more. The upper limit of the width is preferably 500 μm or less. The length (long side) of the terminal (connection pad) is preferably 20 μm or more, more preferably 50 μm or more. The upper limit of the length is preferably 1000 μm or less, more preferably 240 μm or less. The height of the terminal (connection pad) is preferably 6 μm or more for both the terminal on the first electronic component side and the terminal on the second electronic component side. The upper limit of the height is preferably 35 μm or less. The pitch of the terminal (connection pad) is preferably 40 μm or more. Moreover, the upper limit of the pitch is preferably equal to or less than 1500 μm.More specifically, the bonding step is a step of disposing the high-viscosity resin layer on the second electronic component side and bonding it.

[0035] The first electronic component may be a flexible substrate, and the second electronic component may be a ceramic substrate. As described later, the second electronic component is not smooth but has "undulations", which is suitable for the conductive film and anisotropic conductive film of the present invention. The ceramic substrate may be one on which a camera module is mounted or incorporated. When the second electronic component is a ceramic substrate, it usually has undulations of 20 μm or more, specifically, 20 to 50 μm. The waviness of the ceramic substrate can be measured using a surface roughness meter (Kosaka Laboratory Co., Ltd., Surfcorder SE-400). Specifically, the stylus of the surface roughness meter is scanned in the direction of arrangement of the terminals on the ceramic substrate to obtain a profile of the surface unevenness, and the waviness is obtained from the difference between the maximum height and the minimum height in this profile. Measurement may be performed in the same manner as in Japanese Patent No. 6425382.

[0036] The conductive film and anisotropic conductive film of the present invention are necessary when the second electronic component has "waviness", the electrodes (terminals, connection pads) are provided at a height of a predetermined level on a substrate that is not smooth, such as a conventionally used glass substrate or plastic substrate, and the first electronic component has electrodes at a height of a predetermined level, such as a conventionally used FPC. When objects to be connected have such a configuration and are placed opposite each other, it becomes difficult to sandwich conductive particles between the opposing electrodes because of the presence of "waviness" on at least one side. Therefore, it is necessary to design the particle diameter to be 13 μm or more and to take into account the fluidity of the laminated resin layer in order to stabilize the number of conductive particles captured. This is the premise for the design concept of the present invention.

[0037] According to the embodiment's method for manufacturing a connection structure, by using the above-mentioned anisotropic conductive film, the first electronic component and the second electronic component are suitably anisotropically conductively connected to obtain a connection structure having a stable conductive resistance value.

[0038] In particular, when the second electronic component is a substrate (ceramic substrate) having a "waviness" that is not smooth, the terminals on the convex parts of the waviness and the terminals on the concave parts of the waviness are each electrically connected well to the opposing terminals. This is considered as follows. During anisotropic conductive connection, the resin forming the insulating resin layer (high-viscosity resin layer and low-viscosity resin layer) melts and flows. However, in the above-mentioned anisotropic conductive film, the average particle size of the conductive particles is within a specific range, the insulating resin layer is composed of a high-viscosity resin layer and a low-viscosity resin layer having a specific viscosity ratio, and further, the position of the conductive particles in the thickness direction is within a specific range. Therefore, even when the resin melts and flows, the conductive particles on the terminals on the convex parts of the waviness are less likely to flow, making it possible to increase the number of particles captured and achieve a good conductive connection.

[0039] The bonding step may be a step of disposing the low-viscosity resin layer on the second electronic component side and bonding them. In this case as well, the resulting connection structure exhibits a stable conductive resistance value. From the viewpoint of the number of captured particles, the bonding step is preferably a step of disposing the high-viscosity resin layer on the second electronic component side and bonding them.

Example

[0040] Hereinafter, the present invention will be specifically described with reference to examples. <A: Preparation of Insulating Adhesive Layer> Insulating adhesive films A to D were each prepared with a thickness of 16 μm from four types of compositions of formulations A to D shown in Table 1. The formulations in Table 1 are the formulation amounts excluding the solvent content.

[0041] For the four types of prepared insulating adhesive films A to D, a rotational rheometer (manufactured by TA Instruments) was used to heat from room temperature at a heating rate of 10 °C / min, a constant measurement pressure of 5 g, and a measurement plate diameter of 8 mm. The melt viscosity was measured, and the viscosity at 80 °C was read. The results are also shown in Table 1.

[0042]

Table 1

[0043] <B: Preparation of Resin Mold> With a density of 600 pcs / mm 2 A mold with convex portions having a four-sided lattice pattern was produced by cutting a nickel plate. A known transparent resin pellet was melted and poured into the mold, and then cooled and solidified to form a resin mold with concave portions having the same pattern as the convex portions.

[0044] [Example 1] An anisotropic conductive film shown in FIGS. 1 and 2 was produced. The recess of the resin mold obtained in <B: Production of Resin Mold> was filled with conductive particles (average particle diameter: 20 μm, manufactured by Sekisui Chemical Co., Ltd., trade name: Micro Pearl (registered trademark)), and an insulating adhesive film A was placed thereon. The insulating adhesive film A was peeled off with the conductive particles adhering to the surface. With respect to the insulating adhesive film A, while applying heat and pressure to the surface to which the conductive particles adhered, the conductive particles were embedded in the insulating adhesive film A until they reached the desired positions. For the insulating adhesive film A in which the conductive particles were embedded, an insulating adhesive film D previously formed was placed on the surface side where the conductive particles were embedded, and they were pressure-bonded. In the anisotropic conductive film A produced, the insulating adhesive film A constituted a high-viscosity resin layer, and the insulating adhesive film D constituted a low-viscosity resin layer. The conductive particles were arranged at a position where half of the particle diameter protruded to the low-viscosity resin layer side from the boundary between the high-viscosity resin layer and the low-viscosity resin layer. Also, the anisotropic conductive film A had a thickness of 35 μm and a width (short side direction) of 1 mm. As shown in FIG. 3, the produced anisotropic conductive film A (anisotropic conductive film 1) was temporarily adhered so that the alumina ceramic substrate 2 side became the high-viscosity resin 11 layer. Next, the flexible printed circuit board 3 was placed thereon and pressure-bonded under the conditions of 140°C, 6 seconds, and 2 MPa to produce a pressure-bonded sample A. Here, the flexible printed circuit board (FPC) 3 had a copper wiring: line / space = 100 μm / 100 μm, terminal 31 height: 12 μm, and polyimide thickness: 25 μm. Also, the alumina ceramic substrate (PWB) 2 had a tungsten wiring: line / space = 100 μm / 100 μm, terminal (wiring) 21 height: 10 μm, substrate thickness: 0.4 mm, and undulation: 20 μm. When the particle capture rate of the pressure-bonded sample A was calculated, it was 50%. Also, the conductive connections of all channels of the produced pressure-bonded sample A were measurable (30 / 30 ch).

[0045] [Example 2] An anisotropic conductive film B was produced in the same manner as in Example 1, except that an insulating adhesive film C was used instead of the insulating adhesive film A. In the produced anisotropic conductive film B, the insulating adhesive film C constituted the high-viscosity resin layer, and the insulating adhesive film D constituted the low-viscosity resin layer. A pressure-bonded sample B was produced in the same manner as in Example 1, except that the anisotropic conductive film B was used instead of the anisotropic conductive film A. When the particle capture rate was calculated for the pressure-bonded sample B, it was 48%. Also, the conductive connections of the produced pressure-bonded sample B were measurable in all channels (30 / 30ch).

[0046] [Example 3] The anisotropic conductive films shown in FIGS. 1 and 4 were produced. FIG. 4 is a cross-sectional view of the anisotropic conductive film of Example 3 and is a cross-sectional view taken along line A-A shown in FIG. 1. The recesses of the resin mold obtained in <B: Production of Resin Mold> were filled with conductive particles (average particle diameter 20 μm, manufactured by Sekisui Chemical Co., Ltd., trade name: Micro Pearl (registered trademark)), and an insulating adhesive film B was placed thereon. The insulating adhesive film B was peeled off with the conductive particles adhering to the surface. With respect to the surface of the insulating adhesive film B to which the conductive particles adhered, while applying heat and pressure, the conductive particles were embedded in the insulating adhesive film B until they reached the desired positions. For the insulating adhesive film B in which the conductive particles were embedded, an insulating adhesive film C previously formed was placed on the surface side where the conductive particles were embedded and pressure-bonded. In the produced anisotropic conductive film C, the insulating adhesive film B constituted the high-viscosity resin layer, and the insulating adhesive film C constituted the low-viscosity resin layer. The conductive particles were arranged at a position where 1 / 3 of the particle diameter protruded to the low-viscosity resin layer side from the boundary between the high-viscosity resin layer and the low-viscosity resin layer. Also, the anisotropic conductive film C had a thickness of 35 μm and a width (short side direction) of 1 mm. The anisotropic conductive film C thus produced was temporarily attached so that the high-viscosity resin layer was on the alumina ceramic substrate side. Next, a flexible printed circuit board was placed on top and pressure-bonded under conditions of 140°C, 6 seconds, and 2 MPa to produce pressure-bonded sample C. Here, the flexible printed circuit board (FPC) had copper wiring: line / space = 100 μm / 100 μm, terminal height: 12 μm, and polyimide thickness: 25 μm. The alumina ceramic substrate (PWB) had tungsten wiring: line / space = 100 μm / 100 μm, terminal (wiring) height: 10 μm, substrate thickness: 0.4 mm, and waviness = 20 μm. The particle capture rate of the bonded sample C was calculated to be 46%. In addition, the conductive connection of the bonded sample C was measurable in all channels (30 / 30ch).

[0047] [Example 4] Anisotropic conductive film D was produced in the same manner as in Example 1, except that insulating adhesive film B was used instead of insulating adhesive film A, and insulating adhesive film C was used instead of insulating adhesive film D. In the produced anisotropic conductive film D, insulating adhesive film B constituted the high-viscosity resin layer, and insulating adhesive film C constituted the low-viscosity resin layer. A pressure-bonded sample D was prepared in the same manner as in Example 1, except that anisotropic conductive film D was used instead of anisotropic conductive film A. The particle capture rate of the bonded sample D was calculated to be 40%. In addition, the conductive connection of the bonded sample D was measurable in all channels (30 / 30ch).

[0048] [Example 5] An anisotropic conductive film E was produced in the same manner as in Example 1, except that insulating adhesive film C was used instead of insulating adhesive film A. In the produced anisotropic conductive film E, insulating adhesive film C constituted the high-viscosity resin layer, and insulating adhesive film D constituted the low-viscosity resin layer. The anisotropic conductive film E thus produced was temporarily attached so that the high-viscosity resin layer was on the flexible printed circuit board side. Next, an alumina ceramic substrate was placed on top and pressure-bonded under conditions of 140°C, 6 seconds, and 2 MPa to produce a pressure-bonded sample E. Here, the flexible printed circuit board (FPC) had copper wiring: line / space = 100 μm / 100 μm, terminal height: 12 μm, and polyimide thickness: 25 μm. The alumina ceramic substrate (PWB) had tungsten wiring: line / space = 100 μm / 100 μm, terminal (wiring) height: 10 μm, substrate thickness: 0.4 mm, and waviness = 20 μm. The particle capture rate of the bonded sample E was calculated to be 43%. In addition, the conductive connection of the bonded sample E was measurable in all channels (30 / 30ch).

[0049] [Comparative Example 1] An anisotropic conductive film F was produced in the same manner as in Example 1, except that insulating adhesive film A was used instead of insulating adhesive film D. A pressure-bonded sample F was prepared in the same manner as in Example 1, except that anisotropic conductive film F was used instead of anisotropic conductive film A. The particle capture rate of the bonded sample F was calculated to be 35%. In addition, the conductive connection of the bonded sample F was measurable in all channels (30 / 30ch).

[0050] [Comparative Example 2] An anisotropic conductive film was produced as shown in Figures 1 and 5. Figure 5 is a cross-sectional view of the anisotropic conductive film of Comparative Example 2, taken along line AA in Figure 1. The recess of the resin mold obtained in <B: Production of resin mold> was filled with conductive particles (average particle diameter: 20 μm, manufactured by Sekisui Chemical Co., Ltd., trade name: Micro Pearl (registered trademark)), and an insulating adhesive film D was placed thereon. The insulating adhesive film D was peeled off with the conductive particles adhering to the surface. Regarding the insulating adhesive film D, while applying heat and pressure to the surface to which the conductive particles adhered, the conductive particles were embedded in the insulating adhesive film D until they reached the desired positions. Regarding the insulating adhesive film D in which the conductive particles were embedded, an insulating adhesive film A formed in advance was placed on the surface side where the conductive particles were embedded and pressed. In the anisotropic conductive film G produced, the insulating adhesive film A constituted the high-viscosity resin layer, and the insulating adhesive film D constituted the low-viscosity resin layer. The conductive particles were arranged at a position where 2 / 3 of the particle diameter protruded to the low-viscosity resin layer side from the boundary between the high-viscosity resin layer and the low-viscosity resin layer. Also, the anisotropic conductive film G had a thickness of 35 μm and a width (short side direction) of 1 mm. The produced anisotropic conductive film G was temporarily adhered so that the alumina ceramic substrate side became the high-viscosity resin layer. Next, a flexible printed circuit board was placed and pressure-bonded under the conditions of 140 °C, 6 seconds, and 2 MPa to produce a pressure-bonded sample G. Here, the flexible printed circuit board (FPC) had a copper wiring: line / space = 100 μm / 100 μm, terminal height: 12 μm, and polyimide thickness: 25 μm. Also, the alumina ceramic substrate (PWB) had a tungsten wiring: line / space = 100 μm / 100 μm, terminal (wiring) height: 10 μm, substrate thickness: 0.4 mm, and undulation: 20 μm. Regarding the pressure-bonded sample G, when the particle capture rate was calculated, it was 28%. Also, the conductive connections of the produced pressure-bonded sample G were measurable in all channels (30 / 30ch).

[0051] [Comparative Example 3] Anisotropic conductive film H was produced in the same manner as in Example 1, except that conductive particles (average particle diameter 3 μm, manufactured by Sekisui Chemical Co., Ltd., product name: Micropearl) were used instead of conductive particles (average particle diameter 20 μm, manufactured by Sekisui Chemical Co., Ltd., product name: Micropearl). In the produced anisotropic conductive film H, insulating adhesive film A constituted the high-viscosity resin layer, and insulating adhesive film D constituted the low-viscosity resin layer. A pressure-bonded sample H was prepared in the same manner as in Example 1, except that anisotropic conductive film H was used instead of anisotropic conductive film A. In the case of bonded sample H, the small particles could not accommodate the waviness of the ceramic substrate, making it difficult to calculate the particle capture rate. In addition, due to the influence of the waviness of the ceramic, the conductive connection of the bonded sample H could not be measured except for 2 channels of each measurement terminal at the edge, and poor continuity occurred (4 / 30 channels). The evaluation results of the anisotropic conductive films obtained in each of the Examples and Comparative Examples are shown in Table 2. In the anisotropic conductive films obtained in each of the Examples and Comparative Examples, the variation in the position of the conductive particles in the thickness direction was less than 10% of the average particle diameter.

[0052] [Table 2]

[0053] <Evaluation method> (Position of conductive particles in thickness direction, variation width) The anisotropic conductive film was cut at a cross section passing through the line AA in Figure 1, and the cross section was observed under an electron microscope to determine the average value. Specifically, for 50 conductive particles cut so as to pass through the center of the conductive particle sphere in the cross section, the positions of the conductive particles in the thickness direction were measured, and the average value was calculated. The variation range was determined in accordance with the description in the specification. (Particle capture rate) After the temporary attachment, the number of particles on the connection terminal of the alumina ceramic substrate was counted and recorded as "number of particles on terminal before crimping (a)". Next, the flexible printed circuit board was crimped, and after the flexible printed circuit board was peeled off, the number of particles (b) remaining on the connection terminal was counted and recorded as "number of particles on terminal after crimping (b)". Next, the particle capture rate was calculated using the following formula (1). Particle capture rate (%) = Number of particles on terminal after crimping (b) ÷ Number of particles on terminal before crimping (a) ×100 ···(1) However, in Example 5, after temporary bonding, the number of particles on the connection terminals of the flexible printed circuit board was counted and recorded as "number of particles on terminals before crimping (a)". Next, an alumina ceramic substrate was crimped, and after the alumina ceramic substrate was peeled off, the number of particles (b) remaining on the connection terminals was counted and recorded as "number of particles on terminals after crimping (b)". (Conduction resistance) The conductive resistance of the crimped sample was measured using a digital multimeter (34401A, manufactured by Agilent Technologies, Inc.) with a 4-terminal method and a current of 1 mA. A measured resistance value of 2 Ω or less was deemed to be a pass, and a value exceeding 2 Ω was deemed to be a fail. 30 channels were measured, and the number of channels that passed was calculated. (Overall Judgment) A test piece was deemed to have passed if the particle capture rate was 40% or more and if all 30-channel measurements of the conductive resistance were pass. A test piece was deemed to have failed if the particle capture rate was less than 40% or if all 30-channel measurements of the conductive resistance were not pass. [Explanation of symbols]

[0054] 1 Anisotropic conductive film 10 Insulating resin layer 11 High viscosity resin layer 12 Low viscosity resin layer 20 Conductive Particles 2. Alumina ceramic substrate 3. Flexible Printed Circuit Boards 21, 31 terminals

Claims

1. The insulating layer includes a high-viscosity resin layer, an insulating low-viscosity resin layer, and conductive particles having an average particle diameter of 13 μm or more. the low-viscosity resin layer is laminated on the high-viscosity resin layer, The viscosity ratio of the high-viscosity resin layer to the low-viscosity resin layer at 80° C. is 7:4 or more; the conductive particles are disposed on the high-viscosity resin layer side from a position where ⅔ of the particle diameter protrudes from the boundary between the high-viscosity resin layer and the low-viscosity resin layer toward the low-viscosity resin layer side, Conductive film.

2. Conductive particles having an average particle diameter of 13 μm or more and regularly arranged are attached to the surface of an insulating high-viscosity resin layer; applying heat and pressure to the surface of the high-viscosity resin layer to which the conductive particles are attached, thereby embedding the conductive particles in the high-viscosity resin layer; A low-viscosity insulating resin layer is disposed on the surface of the high-viscosity resin layer on which the conductive particles are embedded, and then pressure-bonded to the surface. Alternatively, Conductive particles having an average particle diameter of 13 μm or more and regularly arranged are attached to the surface of an insulating low-viscosity resin layer; applying heat and pressure to the surface of the low-viscosity resin layer to which the conductive particles are attached, thereby embedding the conductive particles in the low-viscosity resin layer; a high-viscosity insulating resin layer is disposed on the surface side of the low-viscosity resin layer in which the conductive particles are embedded, and the layer is pressed against the surface side of the low-viscosity resin layer; A method for manufacturing a conductive film comprising the high-viscosity resin layer, the low-viscosity resin layer, and the conductive particles, the low-viscosity resin layer being laminated on the high-viscosity resin layer, a viscosity ratio between the high-viscosity resin layer and the low-viscosity resin layer at 80°C being 7:4 or more, and the conductive particles being arranged on the high-viscosity resin layer side at a position where 2 / 3 of the particle diameter protrudes toward the low-viscosity resin layer from the boundary between the high-viscosity resin layer and the low-viscosity resin layer.

3. a bonding step of electrically bonding a first electronic component and a second electronic component with a conductive film; the conductive film includes an insulating high-viscosity resin layer, an insulating low-viscosity resin layer, and conductive particles having an average particle diameter of 13 μm or more, the low-viscosity resin layer being laminated on the high-viscosity resin layer, the viscosity ratio of the high-viscosity resin layer to the low-viscosity resin layer at 80° C. being 7:4 or more, and the conductive particles being disposed on the high-viscosity resin layer side from a position where ⅔ of the particle diameter protrudes toward the low-viscosity resin layer side from the boundary between the high-viscosity resin layer and the low-viscosity resin layer. A method for manufacturing a connection structure.

4. The bonding step is a step of disposing the high-viscosity resin layer on the second electronic component side and bonding the high-viscosity resin layer to the second electronic component side. A method for producing the connection structure according to claim 3.

5. The second electronic component is a substrate having a waviness of 20 μm or more. A method for producing the connection structure according to claim 3 or 4.

Citation Information

Patent Citations

  • Filler-containing film

    JP2019031649A

  • Anisotropic conductive film

    JP2019087536A